Transformation of Pancasila Education in Addressing the Moral Crisis of the Young Generation in Indonesia - I Wayan Kandia; I Gede Sujana; I Wayan Eka Santika (CV Tirta Pustaka Press, 2026)
This study analyzes how the transformation of Pancasila Education can address contemporary moral challenges among Indonesian youth, particularly intolerance, digital hate speech, misinformation, and declining civic responsibility in the era of digital globalization. The study is motivated by the increasing emergence of social problems among youth, including intolerance, hate speech, declining social empathy, misinformation, and the weakening of civic responsibility in digital spaces. This study employed a qualitative critical literature review by analyzing academic articles, policy documents, and scholarly publications published between 2020 and 2025 concerning civic education, digital citizenship, and youth morality in Indonesia. The findings eveal that conventional Pancasila Education remains heavily focused on rote memorization and procedural learning, limiting students’ ability to internalize ethical values and apply them critically in contemporary digital and social contexts. Therefore, Pancasila Education should be transformed through dialogical learning, project-based civic engagement, and digital ethics integration to strengthen students’ critical awareness, democratic participation, and responsible digital citizenship. This study concludes that adaptive and transformative Pancasila Education is essential for strengthening national character and preparing socially responsible citizens capable of responding critically to contemporary moral and societal challenges in Indonesia.